Multi-Omics Profiling Identifies Pathways Associated With CD8+ T-Cell Activation in Severe Aplastic Anemia - You, Xing; Yang, Qiong; Yan, Kai; Wang, Song-Rong; Huang, Rong-Rong; Wang, Shun-Qing; Gao, Cai-Yue; Li, Liang; Lian, Zhe-Xiong (Frontiers in Genetics, 2022)
Severe aplastic anemia (SAA) is an autoimmune disease characterized by immune-mediated destruction of hematopoietic stem and progenitor cells. Autoreactive CD8+ T cells have been reported as the effector cells; however, the mechanisms regulating their cell activation in SAA remain largely unknown. Here, we performed proteomics and metabolomics analyses of plasma and bone marrow supernatant, together with transcriptional analysis of CD8+ T cells from SAA patients and healthy donors, to find key pathways that are involved in pathogenic CD8+ T-cell activation. We identified 21 differential proteins and 50 differential metabolites in SAA patients that were mainly involved in energy metabolism, complement and coagulation cascades, and HIF-1α signaling pathways. Interestingly, we found that these pathways are also enriched in T cells from SAA patients by analyzing available single-cell RNA sequencing data. Moreover, CD8+ T cells from SAA patients contain a highly activated CD38+ subset, which was increased in the bone marrow of SAA patients and a murine model of SAA. This subset presented enriched genes associated with the glycolysis or gluconeogenesis pathway, HIF-1α signaling pathway, and complement associated pathways, all of which were of importance in T-cell activation. In conclusion, our study reveals new pathways that may regulate CD8+ T-cell activation in SAA patients and provides potential therapeutic targets for SAA treatment.